The Routledge companion to music and human rights - Fifer, Julian; Impey, Angela; Kirchschlaeger, Peter G.; Nowak, Manfred, 1950-; Ulrich, George (Abingdon, Oxon ; New York, NY : Routledge, 2022)
The Routledge Companion to Music and Human Rights is a collection of case studies spanning a wide range of concerns about music and human rights in response to intensifying challenges to the well-being of individuals, peoples, and the planet. It brings forward the expertise of academic researchers, lawyers, human rights practitioners, and performing musicians who offer critical reflection on how their work might identify, inform, or advance mutual interests in their respective fields. The book is comprised of 28 chapters, interspersed with 23 voices' - portraits that focus on individuals' intimate experiences with music in the defence or advancement of human rights - and explores the following four themes: 1) Fundamentals on music and human rights; 2) Music in pursuit of human rights; 3) Music as a means of violating human rights; 4) Human rights and music: intrinsic resonances.
Keywords: Music -- Social aspects; Music -- Political aspects; Human rights; Music and state; MUSIC / Ethnomusicology